Phytoremediation for dye decolorization - Kamat, Rohit Babli (Kansas State University, 2014)
Synthetic dyes are capable of producing the whole color spectrum on account of their structural diversity but this diversity poses challenges in the degradation of dyeing wastes. Laccases and peroxidases from bacterial or fungal sources and parts of plants in the presence of hydrogen peroxide (H₂O₂) plus a mediator have been exploited in the bioremediation of synthetic dyes. However, intact plants have not found much favor despite their phytoremediation potential. The goal of this research was to further clarify ways by which whole plants bring about decolorization of different types of synthetic dyes. Hydroponically cultivated plants from two dicot families namely Arabidopsis thaliana and sunflowers (Helianthus annuus) were exposed to representative dyes from several classes: monoazo (Methyl Red and Methyl Orange), disazo (Trypan Blue, Evans Blue and Chicago Blue 6B), and arylmethane (Brilliant Blue G, Bromocresol Green, Malachite Green and Phenol Red). Tests were done in presence or absence of externally added H₂O₂, with or without a free radical mediator, 1-hydroxybenzotriazole, using UV-Visible spectrophotometry. The initial rate of decolorization and the overall percentage decolorization was calculated for each dye in the different treatments. Decolorization of the dyes from different classes varied between plant species and depending on the treatment. Except for Methyl Red, all dyes required added H₂O₂ as well as mediator to achieve rapid decolorization. Added H₂O₂ was found to be the limiting factor since it was degraded by plants within a few hours. Both species were able to slowly decolorize dyes upon daily addition of fresh dye even in the absence of added H₂O₂ and mediator, provided that nutrients were supplied to the plants with the dye. A. thaliana was found to be more effective in dye decolorization per gram tissue than sunflower when treated under similar conditions. Analysis of the residual dye solution by ESI/MS did not reveal any potential by-products following the decolorization treatment with plants, suggesting that the plant roots might be trapping the by-products of dye decolorization and preventing their release into the solution. All these findings support the potential application of whole plants for larger scale remediation.
Keywords: Phytoremediation; Textile Dyes; Arabidopsis thaliana; Sunflower; Decolorization; Peroxidase; Biochemistry (0487); Biology, Plant Physiology (0817); Environmental Sciences (0768)